Assessment of Human Health Risk of Zinc and Lead by Consuming F Consuming Food Crops Supplied with Ex ops Supplied with Excessive Fertilizers - Kafeel Ahmad; Asma Ashfaq; Zafar Iqbal Khan; Shahzad Akhtar; Sana Rani; Farzana Siddique; Shamayem Aslam; Ghulam Mustafa; Rana Muhammad Zubair; Hafsa Memona; Aima Iram Batool; Muhammad Nadeem; et al. (Journal of Bioresource Management, 2023)
For the study of heavy metals impact on human beings, areas in Sargodha city that were supplied with various types of fertilizers were chosen. The three industrial areas; (Bhalwal, Sillanwali, and Sahiwal) of this city were explored for research reasons. The researchers wanted to know how much heavy metal was in the soil, food crops, and human. Excess fertilizer use contributes to global pollution. Farmyard manure, urea, and potassium chloride were used on Site 1; urea phosphate, manure, and ammonium sulphate were used on Site 2; and super phosphate, ammonium phosphate, and nitrate phosphate were used on Site 3. Samples of commonly used food crops, their respective soils and blood of residents who ingested the food crops of the studied area were collected. The zinc and lead levels in soil (8.30-16.80 and 1.80-12.71 mg/kg) and food crops (0.26-2.02 and 2.26-4.70 mg/kg) were far lower than WHO permitted limits. Blood mean concentration of both Zn (2.30-4.30 mg/L) and Ni (0.24-0.70 mg/L) were found maximum in residents of Site 3. The values of pollution load index, bioconcentration factor, enrichment factor for both zinc and lead were (0.18- 0.37 a n d 0.220-0.948), (0.027-0.138 and 0.316-1.705), (0.020-0.144 and 0.515-2.780), respectively. Daily intake of metal (0.004-0.008 and 0.001-0.002 mg/kg/day) and health risk index (0.0001-0.016 and 0.005-0.115) values were observed to be lower in individuals for Zn and Pb, respectively. In present work values of all pollution indices were <1 indicated that there was no elevated accumulation of zinc and lead in soil and food crops. So, there would be no human health hazard.